Niat Beli Ulang Generasi Milenial Masa Pandemi Covid-19: Peran Desain Produk, Citra Merek dan Persepsi Harga pada Produk Pakaian - Harsono, Soni; Hadi, Muhamad Ferdian (Fakultas Ekonomi Universitas Samudra, 2024)
This study aims to analyze the effect of product design, brand image, price perception on satisfaction and repurchase intentions for millennial generation apparel products during the Covid-19 pandemic. The research was conducted on 209 consumers using purposive sampling, data were collected through questionnaires, validity and reliability tests were carried out and data were analyzed with SEM WarpPLS. The results showed that product design, brand image and price perception have a significant positive effect on satisfaction and repurchase intentions. Satisfaction mediates the relationship between product design, brand image, price perception and repurchase intention. Product design has a stronger relationship with repurchase intentions. The results of the study can help increase the purchase of clothing products through strategic marketing management that focuses on product design, pricing strategy and brand image.